Dr. Miau – Manejo Interactivo para el Apoyo Universitario (2024)
The project addresses the impact of anxiety and depression on medical students at Universidad Antonio Nariño during their clinical internships. These disorders, stemming from the demanding academic and hospital environment, significantly affect students' emotional well-being and their performance in both modalities. The academic and clinical duties often conflict, as students must balance their responsibilities to achieve the academic success required to pass their semesters, while also developing the skills necessary to become professionals capable of overcoming the various challenges within the medical field.